(untitled) (Research, Society and Development, 2023)
Deep vein thrombosis is an important cause of morbidity and mortality worldwide, especially in the hospital environment, justifying its treatment and also prophylaxis when necessary. The methods of inducing deep vein thrombosis in animals are fundamental for the study of the pathophysiology of the disease, as well as for testing antithrombotic drugs. The objective in this work was to evaluate and compare two methods of inducing deep vein thrombosis in rats: the venous stasis model, widely described in the literature, and the endothelial lesion model, with few studies, especially in rats. male Wistar rats were used for induction of deep vein thrombosis. For stasis, the inferior vena cava was dissected and ligated for 3 hours and after the segment with the vein containing the thrombus was removed. For the endothelial lesion model, a piece of filter paper soaked in FeCl3 was applied for 1 minute and the segment was evaluated after 1 hour. In both models, the wet weight and the area of occlusion were evaluated. For the wet weight, it was obtained by comparing the methods of endothelial injury and stasis, respectively: 17.7mg (±3.0mg) vs. 2.34mg (±1.8mg) with P<0.001. For the area of occlusion, comparing the methods of endothelial injury and stasis, respectively: 85.11% (±9.67%) vs.40.83% (±33.14%), with P<0.05. In all variables, the endothelial lesion method had better results than the venous stasis method, proving to be more reproducible.